Pharmacokinetics of sex steroids in patients with beta thalassaemia major. Issue 7 (July 1993) - Katz, M; De Sanctis, V; Vullo, C; Wonke, B; McGarrigle, H H; Bagni, B
Abstract : AIMS--To assess the pharmacokinetics of oral, intramuscular, or transdermal hormone replacement in patients with beta thalassaemia major. METHODS--Oral (testosterone undecanoate 40 mg) and intramuscular (testosterone propionate 15 mg, phenylpropionate 30 mg, isocaproate 30 mg and decanoate 50 mg) testosterone and transdermal (17 beta oestradiol 25 micrograms and 50 micrograms) oestradiol were evaluated in 21 male (16-29 years) and 11 female (19-26 years) patients with beta thalassaemia major and various forms of hypogonadism. RESULTS--In male patients given oral testosterone, peak testosterone concentrations were observed either two to four hours or seven hours after administration; intramuscular testosterone produced peak values seven days after injection. Transdermal 17 beta oestradiol given to female patients produced a biphasic pattern with an initial peak concentration occurring at 36 hours and a secondary rise at 84 hours. CONCLUSIONS--The results indicate that oral androgens should be given twice daily in cases of hypogonadism, and where growth is incomplete, lower than recommended doses. If intramuscular testosterone is used, smaller doses of 10-25 mg should be given every one to two weeks. Transdermal administration of 25-50 micrograms 17 beta oestradiol generally produces a plasma E2 value in the early to mid-follicular phase range (100-300 pmol/l). This is appropriate in adults but excessive for prepubertal girls. Diffuse iron infiltration of tissues does not seem to interfere with the absorption of androgens and oestrogens from the gut, muscle, or skin.